2021
DOI: 10.1038/s41393-021-00618-4
|View full text |Cite
|
Sign up to set email alerts
|

The challenges characterizing the lived experience of caregiving. A qualitative study in the field of spinal cord injury

Abstract: Study design Qualitative exploratory study. Objectives To explore the lived experience of SCI caregivers, with a focus on the challenges of their role. Setting Caregivers of people with SCI living in the community in Switzerland. Methods Data were collected through semi-structured interviews. Thematic analysis was performed. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It has been reported that spinal cord injuries may ensue psychological problems such as emotional shock, depression, fear of future, loss of dignity, lack of self-care, loss of job, failure to continue education, loss of financial support by monetary institutions, and being deprived of social support [ 34 , 35 ]. Therefore, continuous professional care should be provided to prevent these patients from developing physical and psychological complications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that spinal cord injuries may ensue psychological problems such as emotional shock, depression, fear of future, loss of dignity, lack of self-care, loss of job, failure to continue education, loss of financial support by monetary institutions, and being deprived of social support [ 34 , 35 ]. Therefore, continuous professional care should be provided to prevent these patients from developing physical and psychological complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a difficult question to answer. It is clear that the expressed needs and priorities change from person to person, and are dependent on a variety of factors such as injury level, severity, and time after injury (i.e., acute or chronic) (Glass et al, 1991 ; Anderson, 2004 ; Simpson et al, 2012 ; Trezzini and Phillips, 2014 ; Zanini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 63.3% of family caregivers under the age of 60 were women (80%), and the nature of the relationship with the SCI patient was as a spouse (63.3%), child (13.3%), or parent (10.0%). In many overseas studies [ 24 , 25 , 26 ], family caregivers were mostly women and spouses. These characteristics can be related to the characteristics of patients with SCI with a lower onset age compared to other chronic diseases and a higher frequency of accidents, such as falls or crushing trauma at work [ 17 ].…”
Section: Discussionmentioning
confidence: 99%